Censorium Cinema and the Open Edge of Mass Publicity - Mazzarella, William (Duke University Press, 2013)
In the world of globalized media, provocative images trigger culture wars between traditionalists and cosmopolitans, between censors and defenders of free expression. But are images censored because of what they mean, what they do, or what they might become? And must audiences be protected because of what they understand, what they feel, or what they might imagine?At the intersection of anthropology, media studies, and critical theory, Censorium is a pathbreaking analysis of Indian film censorship. The book encompasses two moments of moral panic: the consolidation of the cinema in the 1910s and 1920s, and the global avalanche of images unleashed by liberalization since the early 1990s. Exploring breaks and continuities in film censorship across colonial and postcolonial moments, William Mazzarella argues that the censors' obsessive focus on the unacceptable content of certain images and the unruly behavior of particular audiences displaces a problem that they constantly confront yet cannot directly acknowledge: the volatile relation between mass affect and collective meaning. Grounded in a close analysis of cinema regulation in the world's largest democracy, Censorium ultimately brings light to the elusive foundations of political and cultural sovereignty in mass-mediated societies
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Okt 2020)
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Motion pictures -- Censorship -- India -- History; Motion pictures -- Political aspects -- India; Motion pictures -- Social aspects -- India; Motion pictures -- India -- History -- 20th century